Intangible cultural heritage of Poland and Belarus in media messages (identification of threats) - Alena Leshkevich (Łódzkie Studia Etnograficzne, 2024)
The article aims to identify threats to intangible cultural heritage generated by the media, which can be used to develop recommendations for a code of ethics for journalists and other individuals working with intangible cultural heritage in the media field. The media is one of the factors potentially threatening intangible cultural heritage as identified in UNESCO documents and research papers. Threats to intangible cultural heritage generated by the media can be categorised into three groups with regard to the subject responsible: 1) threats caused by the inappropriate behaviour of the producers of media materials; 2) threats resulting from the content of media messages; 3) threats resulting from media promotion. The examples analysed are media messages describing annual rituals. The present work offers not only the perspective of a researcher, but also that of a journalist who has been writing about intangible cultural heritage issues for the Belarusian media since 2012.